Research objects of astrophysics as well as some methods of studying (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is about the use of physics to determine the nature of astronomical objects and determine their positions and motions and about several methods for studying astrophysical objects. As astrophysics is a very broad subject, astrophysicists apply concepts and methods from many disciplines of physics, including classical mechanics, electromagnetism, statistical mechanics, thermodynamics, quantum mechanics, relativity, nuclear and particle physics, and atomic and molecular physics. In practice, modern astronomical research often involves a substantial amount of work in the realms of theoretical and observational physics. Some areas of study for astrophysicists include their attempts to determine the properties of dark matter, dark energy, black holes, and other celestial bodies; and the origin and ultimate fate of the universe